Implementation of the Legal Istinbath Method of LBM Mudi Mesra Samalanga - Yasir Nasution; Pagar Pagar; Abdullah Abdullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Istinbath of law which is able to abstract the thoughts of previous scholars and place them according to portions and proposals. On the other hand, various fatwa institutions have also emerged, but the results are very irrelevant and not adaptive to the environment, the ilhaq al-masail bi nadhairiha method was born as one of the methods of legal istinbath carried out by LBM MUDI Mesjid Raya Samalanga. The ilhaq al-masail bi nadhairiha method is not just the result of the thoughts of the LBM board and expert council, but this method is reconstructed from a solid foundation. The basic argumentation of applying istinbath with the ilhaq al-masail bi nadhairiha method is also caused by the opening of the door to interrupt some of the arguments and evidence which are used as a legal basis in the past. The opening of the door can be seen from the existence of several rules which have very universal meanings and are able to adapt according to the development of the times.